Control interno en el área contable de la empresa agroquímicos herrera y asociados, cantón La Maná, provincia de Cotopaxi, periodo 2022. - Pilatasig Ayala, Verónica Mercedes (2023)
The present investigation with the theme of Internal control in the accounting area of Agroquímicos Herrera & Asociados company, in La Maná canton of Cotopaxi province, in 2022, the general objective was to carry out an evaluation of internal control in the accounting area of the Agrochemicals company, for this purpose used types of research such as Bibliographic, field, descriptive, research methods, Inductive-Deductive. Research techniques, together with the interview applied to the owner-manager, and survey to the personnel that works in the entity obtaining data from them, the instrument applied to the personnel was questionnaire of internal control through COSO I, with a population and sample of 6 members and the sample, as a result of the evaluation in the accounting area, was five components, in which, A Confidence Level of 80% was reflected, this being its MODERATE result and a risk level of 20%, giving us LOW. Finally, we proceeded to design the proposal for an internal control model with functions and procedures for the accounting area of Agroquímicos Herrera & Asociados Company. In conlcusion the company does not have the processes to be carried out in the aforementioned area.